Gamified Counseling: Designing Interactive Mobile Tools for Adolescent Mental Health Support in Remote Areas - Ethan Tan; Aarav Sharma; Luis Santos (Journal of Paddisengeng Technology, 2025)
Background. Mental health support for adolescents in remote areas remains a global challenge due to limited access to professional counseling and stigma associated with seeking help. Gamified counseling, which integrates game-based elements into digital platforms, has the potential to enhance engagement, motivation, and accessibility for young users. Purpose. This study aimed to design and evaluate an interactive mobile counseling tool incorporating gamification strategies to support adolescent mental health in remote settings. Specifically, it examined the effectiveness of gamified features in increasing user engagement, perceived usefulness, and psychological well-being. Method. A mixed-method design was employed, involving 200 adolescents from rural communities who participated in an eight-week trial of the mobile counseling application. Quantitative data were collected through validated mental health and user experience questionnaires, while qualitative insights were gathered through interviews and focus groups. Results. The findings reveal that gamified features such as progress badges, storytelling, and interactive challenges significantly improved user engagement and adherence to counseling sessions. Adolescents reported increased motivation to use the application regularly, alongside improved self-reflection and coping strategies. Moreover, participants highlighted the cultural adaptability and accessibility of the platform as key strengths. Conclusion. This study provides evidence that gamified mobile counseling tools can effectively address barriers to mental health support in remote areas. The integration of gamification not only fosters sustained user engagement but also enhances the psychological outcomes of adolescent counseling.